Quality and endosperm storage protein variation in Argentinean grown bread wheat - Lerner, S.E. (2009)
Genetic variability for endosperm storage proteins was analysed in 119 Argentinean grown bread wheat cultivars. For the HMW-GS, three, six and two alleles were observed at theGlu-A1,Glu-B1andGlu-D1loci, respectively, in 17 allelic combinations. The majority of these combinations were considered to be associated with good quality. For the LMW-GS, eight, seven and four alleles were provisionally observed at theGlu-A3,Glu-B3andGlu-D3loci, respectively, in 51 allelic combinations. Regarding quality, the alleles present atGlu-D3were mainly those previously shown to be associated with good quality, whereas atGlu-A3andGlu-B3, some alleles previously associated with poor quality were present at high frequency. Relatively few cultivars carried combinations for all the loci studied that would be expected to be associated with high quality. The mean genetic variation index (H) observed for the glutenin loci (0.589) was similar to values observed in other collections. Unweighted pair-group method using arithmetic averages (UPGMA) of the six loci plus the Chinese Spring-Cheyenne CSS–CNN difference showed that the 119 cultivars fell into 93 distinct combinations. For complete discrimination between all cultivars they would have to be analysed for additional loci. There remains scope for varietal quality improvement within this germplasm pool.